St. Thomas Aquinas on Sacred Scripture and Holiness - Vijgen, Jörgen (Biblica et Patristica Thoruniensia, 2025)
In this article I intend to show that the profound Scriptural roots of St. Thomas’ thought on holiness. Although I will limit myself to three topics, namely (1) the holiness of God, (2) the holiness of creatures and in particular Christ as man and (3) holiness and the moral life, such an analysis reveals three fundamental features of his biblical exegesis. First, reading Sacred Scripture is first and foremost a confessional exegesis. Second, St. Thomas is able to show the fruitfulness of using a Dionysian metaphysics as an explicative tool in addressing the truth of Sacred Scripture. Thirdly, this truth is a Person, the Person of Christ.